The false prison : a study of the development of Wittgenstein's philosophy. - Pears, David, 1921-2009 (Clarendon Press ; Oxford Univ. Press, 1988)
This is the second of two volumes which study the development of Wittgenstein's philosophy. It covers the work that he did after 1929 and traces two lines of thought, one starting from the treatment of solipsism in 'Tractatus', the other developing from the theory of language proposed in that book.